2011
DOI: 10.1186/1471-2164-12-30
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequencing and characterization of floral transcriptome in two species of buckwheat (Fagopyrum)

Abstract: BackgroundTranscriptome sequencing data has become an integral component of modern genetics, genomics and evolutionary biology. However, despite advances in the technologies of DNA sequencing, such data are lacking for many groups of living organisms, in particular, many plant taxa. We present here the results of transcriptome sequencing for two closely related plant species. These species, Fagopyrum esculentum and F. tataricum, belong to the order Caryophyllales - a large group of flowering plants with uncert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 56 publications
6
120
0
1
Order By: Relevance
“…The size and the shape of petals as well as of the rest whorls is genetically determined (Laitinen et al, 2007). However little data are available until now concerning flower proteomic (Dafny-Yelin et al, 2005;Moccia et al, 2009;Sun et al, 2009;Logacheva et al 2011;Zhu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The size and the shape of petals as well as of the rest whorls is genetically determined (Laitinen et al, 2007). However little data are available until now concerning flower proteomic (Dafny-Yelin et al, 2005;Moccia et al, 2009;Sun et al, 2009;Logacheva et al 2011;Zhu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The results of searches for buckwheat floral transcriptome provided nucleotide sequences of 25,435 and 25,401 contigs and 56,874 and 42,913 singletons for Fagopyrum esculentum and Fagopyrum tataricum that has been published by Logacheva et al 26) Each dataset was searched with the TBLASTN algorithm and BioEdit software (http:// www.mbio.ncsu.edu/bioedit/bioedit.html), using the PAM40 matrix, no filter for low-complexity regions and an E-value threshold of 100.…”
Section: Methodsmentioning
confidence: 99%
“…Under these circumstances, it is notable that Logacheva et al 26) have recently reported a buckwheat transcriptome analyzed by de novo sequencing for two close species. Using their data, we searched for novel buckwheat proteins with sequences homologous to SDQTRTGY by TBLASTN (Table 1).…”
Section: Evaluation Of the Cross-reactivity Between Epitope Peptide Smentioning
confidence: 99%
“…Furthermore, the relationship between 3GT expression and RT activity, and its role in controlling rutin biosynthesis should be clarified, despite the lack of reports on RT characterization. However, in flowers of common and Tartary buckwheat, cDNAs with high homology to plant rhamnosyltransferases have been identified in de-novo sequencing analyses using next-generation sequencers (Logacheva et al 2011). Our research group also obtained cDNAs from Tartary buckwheat root with high homology to RT.…”
Section: Synthesismentioning
confidence: 99%